PEMANFAATAN MEDIA SOSIAL DALAM MEMBANGUN IDENTITAS MEREK DIKALANGAN WIRAUSAHA MUDA - Imam Yuwono (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2022)
The increase in the number of social media users is a potential for young entrepreneurs or entrepreneurs, especially to develop their business on social media. 191 million active social media users are a potential target market for the business world. Optimal use of social media for business can benefit business people and improve the welfare of business people and the people involved, such as increasing job opportunities so that they can contribute to community welfare and reduce poverty. One of the efforts that can be done is to build brand identity on social media by young entrepreneurs. As is known, social media users in Indonesia, especially Instagram, are young people. The number of young entrepreneurs doing business on social media is a challenge in itself to be able to compete to attract the attention of consumers, so that the products offered must have an identity so that they are easily recognized among competitors. The research method used is descriptive method, the research subjects are young entrepreneurs who use social media for business for at least 1 year and are selected purposively.